The Correlation Between Employees Skill Level and Rewards They Receive Greatly Impacts Their Overall Performance - Chandro Viryanto Fu; Anoesyirwan Moeins; Yuli Zain (Greenation International Journal of Tourism and Management, 2024)
The objective of this study, conducted within the Marketing Division of PT Coca Cola Amatil Indonesia, is to examine the impact of Compensation and Competence on employee performance. The research method employed for this study included both descriptive and explanatory surveys. The analysis focused specifically on employees within the Marketing Division of PT Coca Cola Amatil Indonesia, with a sample size of 50 individuals. The purpose of this investigation was to establish a causal relationship, while the time horizon considered was cross-sectional. Upon analyzing the findings, it was revealed that employees within the Marketing Division of PT Coca Cola Amatil Indonesia received a satisfactory level of compensation. Additionally, their competence was deemed suitable and sufficient to meet the demands of their roles. Notably, the performance of these individuals within the Marketing Division was found to be exceptionally high. Furthermore, it was determined that both compensation and competence had a simultaneous impact on employee performance. It is important to highlight that the influence of compensation on performance outweighs that of competency. Enhancing employee performance is of utmost importance, as it is greatly influenced by the level of compensation they receive. Keeping this in mind, it is advisable to ensure that the Marketing Division of PT Coca Cola Amatil Indonesia receives compensation that adheres to regulations, including an augmentation of supplementary benefits. This will enable them to execute their responsibilities in a more proficient and polished manner